Пам’яті Геннадія Михайловича Зінов’єва (18.04.1941–19.10.2021) - Borisenko, O.A.; Gorenstein, M.I.; Gusynin, V.P.; Zagorodny, A.G.; Zasenko, V.I.; Izotov, Yu.I.; Kukhtin, V.V.; Lev, B.I.; Loktev, V.M.; Martynov, E.S.; Pashitskii, E.A.; Perepelytsya, S.M.; et al. (Publishing house "Academperiodika", 2021)
-